THE INFLUENCE OF COUNSELING OR LEAFLETS ON TEENAGERS' KNOWLEDGE ABOUT HIV AIDS AT MUHAMMADIYAH 3 YOGYAKARTA HIGH SCHOOL - Reka Julia Utama; Gadis Halizasia; Ferdi Riansyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The incidence of HIV/AIDS from year to year has increased worldwide WHO stated that by the end of 2015, at least 36.9 million people are affected by HIV/AIDS and keep increasing in prevalence. The aim of this study is to know theeffect of the socialization or leaflet to the knowledge of the adolescent about HIV AIDS in SMA Muhammadiyah 3 Yogyakarta. This study uses Quasy Experiment Two group pretest-posttest methods with 60 respondents selected with proportional sampling, the data were analyzed using T-Test. This study shows that the mean value of the pre-test and post-test in the group with socializationis 40.93, while the means value of the group with leaflet is 33.87, with the difference of 7.067 and P-value 0.01, which shows that the transfer of knowledge of the adolescent given socialization is 7 times more effective than the adolescent with leaflet. Socialization is 7 times more effective compared to the leaflet in transferring knowledge about HIV AIDS at SMA Muhammadiyah 3 Yogyakarta.